The structure and behaviour of the Whooper Swan population wintering at Caerlaverock, Dumfries and Galloway, Scotland: an introductory study - Black, Jeffrey M; Rees, Eileen C (Wildfowl, 1984)
Since the mid-1970s there has been an annual increase in the number of Whooper Swans Cygnus cygnus wintering on the Eastpark Wildfowl Refuge, Caerlaverock, Dumfries and Galloway, Scotland, which is now a site of international importance for the species. Between 1979-80 and 1983-4, 189 Whooper Swans were marked with leg rings at Eastpark. Overall, 78% of the ring swans returned to Eastpark for at least one winter and 40% of the swans which were ringed in 1979080 returned for four successive years. Swans first identified as pairs or families were more likely to return than singles and yearlings. There was no significant difference in the return rates of male and female swans. The population contained an equal distribution of the two sexes. Singles formed the largest social class (32.5%) and showed little annual variation. The proportion of swans with cygnets fluctuated, but on average about 30% of the known pairs brought young. Mean brood size ranged from 2.0 (198304) to 3.5 (1982-3). Females paired earlier than males. Only one known-aged swan (five-year-old female) has returned to the wintering grounds with offspring. Two swans (one male and one female) were firmly paired at one year old (second winter). Mates are frequently chosen from the wintering flock. The main arrival period at Eastpark was during October and most swans departed in March. Yearlings arrived first, followed by families, then by pairs and singles. There was no significant difference in the departure patterns of the different classes. Single swans spent a higher proportion of time away from the reserve than other classes. Sighting data support the view that Whooper Swans wintering at Eastpark are from Icelandic breeding grounds and that the Caerlaverock area is usually the final wintering destination for most of these birds, rather than a staging site during migration to Ireland. Whooper Swans spent the majority of the winter season on the Eastpark Refuge but also made use of the surrounding arable land especially in the autumn and spring. Bewick’s Swans Cygnus columbianus bewickii made significantly less use of the refuge. In October, Whooper Swans fed mainly on barley stubble and old grasses, moving to potatoes and aquatic river plants in November and December. Newly-planted winter grass was favoured by the swans from February until they left the area in late March and April. Grass species were identified from droppings. Activity budgets showed that Whooper swans spent most time on the refuge feeding and loafing on water (both 30%) and the remainder of the day was spent in comfort behaviour (22%) and grazing (8%). A comparison of activity budgets and their seasonal variations was made with Bewick’s and Mute Swans Cygnus olor. Observations on the Whooper Swans at Islesteps (11 km NW of Eastpark) indicate that a much higher proportion of the day was spent grazing (45%) than at Eastpark (16% combined grazing and feeding in water), and suggestions are made that Eastpark swans may benefit from the longer periods of loafing on water. There was no difference in the frequency of aggression between the refuge and Islesteps, although intense periods of interaction occurred at Eastpark after the grain was put out. Aggression increased on the refuge during spring because of coprophagy on faeces which contained large amounts of undigested barley.